Cyclosporin A and intravenous immunoglobulin treatment in polymyositis/dermatomyositis. Issue 1 (1st January 2002) - Danieli, M G; Malcangi, G; Palmieri, C; Logullo, F; Salvi, A; Piani, M; Danieli, G
Abstract : Objective: To describe the treatment of polymyositis (PM) and dermatomyositis (DM) with prednisone (PRED) and cyclosporin A (CSA) alone or associated with intravenous immunoglobulin (IVIg) and plasmapheresis (PEX). Methods: Between 1992 and 1999 CSA and PRED were used to treat 20 patients with idiopathic myositis (12 with DM, eight with PM), diagnosed according to the Bohan and Peter criteria. In patients with refractory or relapsed disease, IVIg was added alone (seven cases) or synchronised with PEX (six cases). A standardised protocol was used to evaluate the patients, and assess disease activity and treatment response. Results: Despite a transient response to PRED and CSA in 16/20 cases, this combination did not induce full remission in 13/20 cases, which led to the IVIg trial with or without PEX. Patients receiving PRED and CSA plus IVIg had a significantly higher probability of maintaining complete remission at the end of the four year follow up period than those treated with PRED and CSA alone (p<0.001). No further benefit was added by the PEX. The presence of arthritis significantly correlated with a poorer response to treatment (p<0.05). Adverse effects were gingival hyperplasia (one patient) and transient renal dysfunction (one). Conclusions: This open study suggests that combined treatment with PRED, CSA, and IVIg is useful in patients with myositis, even those with refractory or relapsed disease; no increase in the number or type of side effects is seen.